(untitled) (Global Journal of Science Frontier Research, 2015)
According to Planck Mission, the observable universe comprises of 26.8% dark matter, 68.3% dark energy and 4.9% ordinary matter. By calibrating or fine-tuning a speculative equation of matter composition, this work confirmed observable consequences of our theoretical insights, as the equation was solved for roots corresponding to 4.915% ordinary matter, 26.785% dark matter, and 68.300% dark energy, thus achieving nearly 100% overlap with the Planck Mission Statement. The equation also confirmed some of the earlier NASA Science Astrophysics statements.